The Translocator Protein 18 kDa (TSPO) and Its Role in Mitochondrial Biology and Psychiatric Disorders - M. Milenkovic, Vladimir; Rupprecht, Rainer; H. Wetzel, Christian (Mini Reviews in Medicinal Chemistry, 2015)
The translocator protein 18 kDa (TSPO) is localized in the outer mitochondrial membrane of many cell types and its expression is found to be up-regulated under various pathological conditions such as cancer, inflammation, mechanical lesions, and neurological diseases, e.g. amyotrophic lateral sclerosis (ALS). Its primary function is to mediate the transport of cholesterol into the inner compartments of mitochondria. Moreover, TSPO is interacting and building up functional complexes with other mitochondrial proteins such as the voltage-dependent anion channel (VDAC), the adenine nucleotide transporter (ANT), hexokinase I and II and Glycogen synthase kinase 3 beta (GSK3β). This mini review will focus on the role of TSPO as a central regulator of mitochondrial function with regard to pathologic states and as a target for new therapeutic strategies for the treatment of psychiatric disorders.
Keywords: TSPO